The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10499-007-9161-7
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite marker isolation and cultured strain identification in Carassius auratus gibelio

Abstract: Microsatellites have become the preferred molecular markers for strain selection and genetic breeding in fish. In this study a total of 105 microsatellites were isolated and identified in gibel carp (Carassius auratus gibelio) by microsatellite sequence searches in GenBank and other databases and by screening and sequencing of positive clones from the genomic library enriched for AG and GATA repeats. Moreover, nineteen microsatellites were randomly selected to design locus-specific primer pairs, and these were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…S1). Previous studies had shown that triploid individuals with identical transferrin phenotype patterns might be regarded as one gynogenetic clone (Yang et al, 2001), and the clone identity has been confirmed by SCAR markers (Zhou et al, 2001), microsatellites (Guo and Gui, 2008), mtDNA sequences (Li and Gui, 2008), and AFLP profiles (Wang et al, 2011), which is consistent with the standardizing methods suggested by Arnaud-Haond et al (2007). Thereby, about 64 various clones could be distinguished from the triploid form, and their geographical distribution in the 4 sampled sites was detailed in Electronic supplementary material, Table S3.…”
Section: Transferrin Phenotype Pattern Diversity and Various Clone DImentioning
confidence: 80%
See 1 more Smart Citation
“…S1). Previous studies had shown that triploid individuals with identical transferrin phenotype patterns might be regarded as one gynogenetic clone (Yang et al, 2001), and the clone identity has been confirmed by SCAR markers (Zhou et al, 2001), microsatellites (Guo and Gui, 2008), mtDNA sequences (Li and Gui, 2008), and AFLP profiles (Wang et al, 2011), which is consistent with the standardizing methods suggested by Arnaud-Haond et al (2007). Thereby, about 64 various clones could be distinguished from the triploid form, and their geographical distribution in the 4 sampled sites was detailed in Electronic supplementary material, Table S3.…”
Section: Transferrin Phenotype Pattern Diversity and Various Clone DImentioning
confidence: 80%
“…In the past decade, a lot of genetic knowledge including molecular basis of reproduction trait and numerous polymorphic DNA markers has been investigated and characterized from the triploid form (Gui and Zhou, 2010;Gui and Zhu, 2012). Similar to other polyploid salamanders, frogs and fish (Lampert and Schartl, 2010;Schlupp, 2005;Stöck et al, 2012), the triploid form can also reproduce by sperm-dependent gynogenesis, and many diverse gynogenetic clones have been discriminated by different genetic markers, such as transferrin Yang et al, 2001, RAPD and SCAR markers (Zhou et al, 2001(Zhou et al, , 2000b, microsatellite (Guo and Gui, 2008) and mtDNA sequence (Apalikova et al, 2008;Brykov et al, 2005;Li and Gui, 2008). Interestingly, a minor but significant portion (approx 1-10%) of triploid males were found in the triploid form, and normal sperm production and their sexual reproduction ability have been demonstrated by experimental propagation and genetic analysis in the triploid form (Gui and Zhou, 2010;Peng et al, 2009;Sun et al, 2010;Zhou et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…In polyploid gibel carp (Carassius auratus gibelio), several significant molecular markers including transferrin alleles [11], SCAR [12], microsatellites [13], AFLP [14] and mitochondria DNA sequences [15,16] were identified, and dual modes of unisexual gynogenesis and sexual reproduction were revealed by these markers [17,18]. Significantly, the unique dual reproduction mode, as commented by Avise (2008), was the first documented instance in vertebrates [19], and the discovery firstly explained reproduction mechanism of high genetic diversity and an evolutionarily long-lived timescale of unisexual species [18].…”
Section: Genome Technologies Of Aquaculture Animalsmentioning
confidence: 99%
“…It has been observed widely in many countries of the Eurasian continent (Gui and Zhou, 2010), such as in Britain (Hanfling et al, 2005), Italy (Hanfling et al, 2005), Hungary (Toth et al, 2005), Germany (Hanfling et al, 2005), Croatia (Jakovlic and Gui, 2011), Greece (Liasko et al, 2010), Kazakhstan (Sakai et al, 2009), Russia (Abramenko et al, 2004;Jiang et al, 2013), China (Gao et al, 2012;Jiang et al, 2013;Li and Gui, 2008), and Japan (Takada et al, 2010). Similar to other unisexual polyploid vertebrates, the polyploid gibel carp can reproduce by spermdependent gynogenesis, and many diverse gynogenetic clones have been discriminated by biological traits and molecular markers (Bai et al, 2011;Gui and Zhou, 2010;Guo and Gui, 2008;Yang and Gui, 2004;Zhou et al, 2000a). In contrast to other unisexual all-female vertebrate animals, males have been discovered from the natural triploid populations in northeast Asia (Jiang et al, 2013), Russia (Abramenko et al, 2004), Greece (Liasko et al, 2010) and Croatia (Jakovlic and Gui, 2011), and multiple reproduction modes, including sexual reproduction, gynogenesis, or even androgenesis, have been demonstrated by experimental propagation and molecular marker analysis to coexist in the polyploid gibel carp (Gui and Zhou, 2010;Wang et al, 2011;Zhou et al, 2000b).…”
Section: Introductionmentioning
confidence: 99%